The Effect Of Plyometric Training Variations On The Jumping Smash Ability Of Divo Club Volleyball Athletes (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to investigate the effect of plyometric training variations on the jumping smash ability of athletes in the Divo Volleyball Club. Plyometric training is widely recognized as an effective method to improve explosive power, which plays a crucial role in performing jumping smashes in volleyball. The research employed an experimental approach with a one-group pretest-posttest design involving 16 female athletes. Data were obtained through jumping smash performance tests administered before and after the training intervention. The treatment consisted of structured plyometric training variations designed to enhance lower-body power and vertical jump capability. The results of the analysis revealed a significant improvement in jumping smash ability after the intervention, with the mean pretest score of 222.31 increasing to 256.75 in the posttest (p = 0.000). These findings confirm that plyometric training variations are highly effective in enhancing the technical performance of jumping smashes among volleyball athletes. The study highlights the importance of incorporating diverse plyometric exercises into regular training programs as a strategic approach to maximize athletes’ attacking performance and overall competitive readiness in volleyball.